(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The density is assumed to be a complex parameter of quality wood. On the one hand, it depends on the anatomical structure of the wood, the other largely determine all other mechanical properties and influence the processing and use of wood. Work considered the density of oak wood, sourced from different habitats in the country and its distribution in the radius of the stem. The influence of age, the width of the annual ring, habitat and altitude